2010
DOI: 10.1111/j.1365-2591.2009.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adhesive system type and root region on the push‐out bond strength of glass–fibre posts to radicular dentine

Abstract: The use of BisCem and All Bond SE/Duo-Link combination with their simplified application procedures may be considered an alternative to the currently used systems for luting glass-fibre posts in root canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 34 publications
5
33
1
3
Order By: Relevance
“…Despite the methodological differences, previous studies (2,3,20,(22)(23)(24) have also verified higher bond strength in the coronal root canal region. Analysis of the failure modes confirm the lower values of adhesion in the apical region, with predominance of adhesive and mixed-type failures in this region.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the methodological differences, previous studies (2,3,20,(22)(23)(24) have also verified higher bond strength in the coronal root canal region. Analysis of the failure modes confirm the lower values of adhesion in the apical region, with predominance of adhesive and mixed-type failures in this region.…”
Section: Discussionmentioning
confidence: 95%
“…Unlike Yoldas and Alaçan (19), who found that the polymerization of resin material has occurred at a 15 mm depth, the present results suggest that the polymerization of cement was compromised in the apical region, where the light has a reduced range. The differences among post/canal regions can be explained by the regional differences in the root dentin such as quantity, volume and orientation of the tubules toward the apical portion, apical sclerosis (20), the high cavity configuration factor, the difficulty in visualization and access to this region, restrictions in the flow and distribution of material in the apical region that makes more bubbles and voids within the cement (21) and presence of smear layer formed during the post space preparation, which could not be modified by the adhesive cement or removed by irrigation with sodium hypochlorite and EDTA (22). Another aspect to be considered is the limited light transmission capability of the fiber post used in the present study (22), with impaired polymerization of cement and bonding quality in the apical portion (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that such lower degrees of conversion result in lower bond strengths at those root-canal depth levels at which photoactivation is ineffective. [17][18][19][20][21][22][23][24][25][26]30 In the group in which the light was directly applied to the apical area of the root canal, the bond strength showed significant improvement. Studies have shown that in the apical third, dentin exhibits conditions that are less favorable for adhesion, 14,16 such as a lower number of dentinal tubules, [12][13][14] and a greater probability of presenting endodontic treatment remnants.…”
Section: Discussionmentioning
confidence: 99%
“…16 Techniques for post cementation based on resin infiltration in the interior dentinal tubules are more sensitive and less predictable in the apical area. 14,16 Although several studies [17][18][19][20][21][22][23][24][25][26] have shown that resin cement bond strengths inside the apical third of the post space preparations are lower than those at the cervical third, some authors [27][28][29] were unable to confirm this difference. Thus, it is important to investigate the factors influencing bond strength of resin cements in the apical third of the post space preparation, emphasizing the role of photoactivation and dentinal substrate in that root canal area.…”
Section: Introductionmentioning
confidence: 99%
“…5 Because the accessibility of light energy passing through a deep and narrow root canal space is restricted, the bond strength gradually decreases from the coronal to the apical surface of the root canal. 6 Therefore, light irradiation of an adhesive seems to be important for core build-up systems to achieve good adhesion to root canal dentin. 7 Because there is little information on the mechanism by which light irradiation of adhesives affects the dentin bond strength of dualcure direct core build-up systems, determining the influence of light intensity on the dentin bonding characteristics of these resin systems is required.…”
Section: Introductionmentioning
confidence: 99%